2008
DOI: 10.1534/genetics.108.086637
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Deleterious Mutations

Abstract: The evolutionary advantage of sexual reproduction has been considered as one of the most pressing questions in evolutionary biology. While a pluralistic view of the evolution of sex and recombination has been suggested by some, here we take a simpler view and try to quantify the conditions under which sex can evolve given a set of minimal assumptions. Since real populations are finite and also subject to recurrent deleterious mutations, this minimal model should apply generally to all populations. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 28 publications
12
47
0
Order By: Relevance
“…We found that the benefit of sex increased with population size, in agreement with earlier studies (Iles et al 2003;Keightley and Otto 2006;Gordo and Campos 2008;Hartfield et al 2010). Those studies identified Hill-Robertson interference as the principal cause of this pattern.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the benefit of sex increased with population size, in agreement with earlier studies (Iles et al 2003;Keightley and Otto 2006;Gordo and Campos 2008;Hartfield et al 2010). Those studies identified Hill-Robertson interference as the principal cause of this pattern.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Muller's ratchet is strongest in small populations that often experience deleterious mutations, whereas the Fisher-Muller effect is strongest in large populations that often experience beneficial mutations. The increase in the strength of the Fisher-Muller effect between beneficial mutations with population size is intuitive because population size (N) affects the beneficial mutation supply rate (NU b ; where U b is the beneficial mutation rate).More surprising is the recent finding from evolutionary simulations that interference between deleterious mutations can, on its own, also generate a large benefit of sex that increases with population size (Otto and Barton 2001;Iles et al 2003;Barton and Otto 2005;Keightley and Otto 2006;Gordo and Campos 2008;Hartfield et al 2010). This finding is surprising because neither Muller's ratchet (Muller 1964;Haigh 1978;Gordo and Charlesworth 2000) nor background selection Kaplan 1994, 1995) is expected to increase in strength with population size.…”
mentioning
confidence: 99%
“…Strong modifiers that substantially increased the sex rate exhibited a higher advantage than weak modifiers. This result was the same as in haploids, in which the advantage of a sex (recombination) modifier begins to increase as its strength increases at p sex E0.01 (Gordo and Campos, 2008).…”
Section: Selection On a Recombination Modifiersupporting
confidence: 59%
“…However, Otto (2003) did not investigate the effects of finite population size on the evolution of sex, which is a potentially important factor that affects selection for segregation. In finite populations, the interaction between drift and selection strongly favors a recombination modifier (Keightley and Otto, 2006;Gordo and Campos, 2008). Nevertheless, the mechanism by which drift influences the conditions favoring segregation remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Second, our analysis has focused on asexual populations and neglected recombination. Since even weak recombination has the potential to significantly slow Muller's ratchet, it would be interesting to generalize our dynamic balance to include its effects (Bell 1998;Gordo and Campos 2008). Increasing recombination rates would presumably allow the population to maintain better-adapted genotypes in this steady state.…”
Section: Discussionmentioning
confidence: 99%